Should we make or buy? An update and review - Rubén Medina Serrano; María Reyes González Ramírez; José Gascó (European Research on Management and Business Economics (ERMBE), 2018)
Whether firms should perform manufacturing activities on their own or buy them from an external provider is a strategic question that many managers from all firm areas have historically asked themselves. The present paper seeks to address this question by developing a theoretical framework which can help managers evaluate sourcing decisions. After discussing a make-or-buy literature review on 7 prestigious academic journals, the most relevant determinants and theories supported from the literature are identified and illustrated within this framework. The results are subsequently outlined, our research work concluding with a reflection on the extent to which this paper can improve the academic understanding of make-or-buy approaches. Our results suggest that practitioners should combine the resource-based view, strategic management and transaction cost economics theories in order to assess manufacturing location decisions.
Keywords: 650; Make-or-buy; Decision-making; Outsourcing; Plural/hybrid sourcing; Literature review